Computationally Designed Peptide Inhibitors of the Ubiquitin E3 Ligase SCFFbx4. Issue 4 (11th February 2013) - Lee, Junglim; Sammond, Deanne W.; Fiorini, Zeno; Saludes, Jonel P.; Resch, Michael G.; Hao, Bing; Wang, Wei; Yin, Hang; Liu, Xuedong
<x xml:space="preserve">Abstract</x> A structure‐based computational approach was used to rationally design peptide inhibitors that can target an E3 ligase (SCFFbx4)–substrate (TRF1) interface and subsequent ubiquitylation. Characterization of the inhibitors demonstrates that our sequence‐optimization protocol results in an increase in peptide–TRF1 affinity without compromising peptide–protein specificity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>